Ideology and the Kazakh Press (Content Analysis of «Qazaq аdebieti» materials) - Kaiyrbek , М.Ә. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
This article presents a comparative analysis of the evolution of state ideological concepts in Kazakhstan from 2015 to 2025, where 2015–2019 marks the late presidency of N. Nazarbayev and 2019–2025 represents the first five years of K.-J. Tokayev’s rule. The study employs a decade-long content analysis of publications in the newspaper "Qazaq ádebieti" (Kazakh Literature), selected as a primary platform for the views of Kazakh intellectuals. A radical paradigm shift is revealed: from the dominance of historical-conservative narratives under Nazarbayev (Rukhani Zhangyru, Máńgilik El) to Tokayev’s pragmatic socio-legal agenda (Just Kazakhstan, Taza Qazaqstan, Rule of Law, Adal Azamat [Man of integrity], rehabilitation of the Alash heritage, digitalization, and AI). The research highlights the transformed role of intellectuals: from "guardians of tradition" to agents modernizing public consciousness. Global and domestic challenges (the pandemic, the Ukraine war, January 2022 events) accelerated shifts toward economic sovereignty and social justice. The study’s novelty lies in proving a direct correlation between political changes, the evolution of media discourse, and reimagined national identity.